Efficacy of a Standardised Patient Simulation Programme for Chronicity and End-of-Life Care Training in Undergraduate Nursing Students - Silvia Escribano (MDPI AG, 2021)
Background: Standardised patient simulations seem to be useful for improving the communication skills of health sciences students. However, it is important to define the effectiveness of these types of interventions in complex scenarios linked to disease chronicity and end-of-life contexts. Methods: A quasi-experimental study with pre- and post-intervention measures was carried out in a single group. A total of 161 nursing students completed different assessment instruments to measure their attitudes towards communication (Attitude Toward Communication Scale), self-efficacy (Self-Efficacy of Communication Skills, SE-12), and communication skills (Health Professionals Communication Skills Scale, EHC-PS) before and after simulation training with standardised patients. The objective of the program was to train students in non-technical skills for complex situations involving chronicity and end-of-life care. It comprised eight sessions lasting 2.5 h each. Results: The results showed notable baseline gender differences in attitudes towards communication and in the informative communication dimension, with women obtaining higher scores. The participants’ self-efficacy and communication skills significantly improved after completing the intervention, with no significant differences being found for the attitudes towards communication variable. Conclusion: The standardised patient simulation programme for complex scenarios related to chronicity and end-of-life contexts improved communication self-efficacy and communication skills in these nursing students. In future work it will be important to analyse the influence of gender and attitudes towards communication as variables in the learning of communication skills in nursing students.